2014
DOI: 10.1007/s13369-014-1527-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-area Multi-fuel Economic–Emission Dispatch Using a Generalized Unified Power Flow Controller Under Practical Constraints

Abstract: This paper presents a novel optimization algorithm for the multi-area multi-fuel economic-emission dispatch problem and total power loss objective. The proposed method uses the uniform distribution to determine the control parameters and employs a two-stage initialization process. This enables various objectives to be optimized under practical constraints and device limits. We formulate a realistic generation cost that includes the cost of reactive power generation, shunt power injections, and total power loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 71 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…In 2015, an optimal allocation strategy based on transmission line loadings and busbar voltage range changes was also proposed to improve the system's safety by minimizing the system's power loss in the presence of GUPFC using Particle Swarm Optimization (PSO) method [10]. In the same year, 2015, a novel optimization plan was proposed to solve the Multi-area Multi-fuel Economic-Emission Dispatch problem and minimize the total power losses [11]. This method utilizes a uniform distribution to determine the control parameters and uses a two-step initialization process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2015, an optimal allocation strategy based on transmission line loadings and busbar voltage range changes was also proposed to improve the system's safety by minimizing the system's power loss in the presence of GUPFC using Particle Swarm Optimization (PSO) method [10]. In the same year, 2015, a novel optimization plan was proposed to solve the Multi-area Multi-fuel Economic-Emission Dispatch problem and minimize the total power losses [11]. This method utilizes a uniform distribution to determine the control parameters and uses a two-step initialization process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 The power carrying capacity of the transmission line is restricted through factors like thermal, voltage-drop, stability, and so forth. 12 Based on the line factors as well as location thermal range is affected and the line and load factors, the voltage are dropped. 13,14 The behavior of power system as well as line factors are also affects the stability of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have worked on optimizing dispatching in the presence of these devices in order to obtain better results. This is the case of Suresh et al [10] who integrated the Generalized Unified Power Flow Controller (GUPFC) into the DEE problem with the aim of reducing the total cost of production, active losses and gas emissions. The algorithm they used is the NSUDTPSO (Non-dominated Sorting Uniformly Distributed Two-stage Particle Swarm Optimization).…”
Section: Introductionmentioning
confidence: 99%
“…Tests carried out on IEEE 30-bus networks have shown that with the insertion of this FACTS, active losses in the network are reduced as well as the total production cost and gas emissions. In 2016, Vijayaraj et al [11] did the same work as [10] but using the improved bat algorithm (IAB). The tests were carried out on the 30-node IEEE network with and without UPFC.…”
Section: Introductionmentioning
confidence: 99%